Triazole tethered isatin-coumarin based molecular hybrids as novel antitubulin agents: Design, synthesis, biological investigation and docking studies. Issue 17 (1st September 2017) - Singh, Harbinder; Singh, Jatinder V.; Gupta, Manish K.; Saxena, Ajit K.; Sharma, Sahil; Nepali, Kunal; Bedi, Preet Mohinder S.
Graphical abstract: Highlights: Design of isatin-coumarin hybrids based on the cytotoxicity of each pharmacophore. Synthesis of 28 novel isatin-coumarin hybrids using click chemistry approach. Biological evaluation of hybrids against a panel of four human cancer cell lines. Tubulin polymerization inhibition by the most cytotoxic hybrids. Docking of the most potent hybrid at curcumin binding site of tubulin. Abstract: In an attempt to develop potent anti-tubulin agents against most dreadful disease cancer, a library of 28 novel triazole tethered isatin-coumarin hybrids were synthesized by click chemistry approach. Synthesized hybrids were characterized and evaluated against a panel of human cancer cell lines viz. THP-1, COLO-205, HCT-116 and PC-3. Biological assay unveiled that, compoundsA-1 toA-6, B-1 toB-4 andC-1 toC-3 displayed significant inhibitory potential against THP-1, COLO-205 and HCT-116 cell lines which were more sensitive towards the designed hybrids. PC-3 among these cell lines was found to be almost resistant. Established SAR revealed marked dependence of the cytotoxic activity on the type of substituent on isatin and the length of carbon-bridge connecting isatin moiety with triazole ring. Unsubstituted isatin and two carbon-bridge were found to be crucial for cytotoxicity. Three most potent hybrids(A-1, A-2 andB-1) were further tested for tubulin polymerization inhibition. Among these three compounds, A-1 found to be endowed with most prominent tubulin polymerization inhibition potential with IC50 value of 1.06 µM which was further confirmed by using confocal microscopy. Possible binding interactions between the most potent hybrid moleculeA-1 and tubulin were also divulged by molecular modeling studies.